PERAN STRATEGIS DPL DALAM MBKM ASISTENSI MENGAJAR: STUDI DI SMAN 19 PEKANBARU TA. 2024/2025 - Siti Nazhifah; Nabila Afifah Azuga; Agus Baharudin; Tiara Mahardika; Baik Budi (Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
The transformation of higher education in Indonesia through the Merdeka Belajar Kampus Merdeka (MBKM) policy has encouraged stronger integration between academic learning and real-world practice in the community, one of which is through the Teaching Assistance program. This article describes the strategic role of DPL or Field Supervisors in guiding students during the implementation of the Teaching Assistance Program at SMAN 19 Pekanbaru during the second semester of the 2024/2025 academic year. A descriptive-qualitative approach was used to explore the contributions of DPL as pedagogical facilitators, reflective evaluators, institutional liaisons, enhancers of soft skills and professionalism, and integrators of technology use for students. The data collection methods employed in this study included observation, interviews, documentation, guidance notes, and reflections throughout the program. The research findings indicate that the presence of DPL significantly contributes to strengthening students' pedagogical competencies, shaping professional character, and bridging communication between universities and partner schools. In addition to positively impacting the quality of student learning, this program also supports the optimal use of technology and active learning in schools. The research findings also emphasize that the success of the MBKM program implementation heavily depends on the synergy between students, DPL, and school stakeholders, as well as the active involvement of DPL in all stages of the activity.